PENGARUH INFLASI TERHADAP PRODUK DOMESTIK BRUTO (PDB) INDONESIA PADA PERIODE TAHUN 2010-2020 - Dikson Silitonga (ESENSI: Jurnal Manajemen Bisnis, 2021)
The economic growth of a country can be shown by the increasing of its gross domestic product (GDP). Apart of income items such as consumption, investment, government expenditures, and net export, the GDP is also influenced by other factors. Based on my quantitative study by using the simple regression analysis, Inflation has a simultaneous influence toward GDP. Inflation has a negative impact partially toward the Indonesia's GDP. The inflation acts as a factor that can explain the changing of GDP of Indonesia partially.